THE IMPACT OF ECONOMIC EDUCATION ON THE ENTREPRENEURIAL MINDSET OF STUDENTS OF STATE UNIVERSITY OF SURABAYA - Yulia Dwi Rahmawati; Riza Yonisa Kurniawan; Albrian Fiky Prakoso (Journal of Business And Entrepreneurship, 2026)
Economic education is very important to shape the entrepreneurial mindset of students. The purpose of this study is to find out how economic education has an impact on the development of entrepreneurial mindset of students of the State University of Surabaya. This research uses a qualitative approach, namely collecting data through observation and in-depth interviews with students enrolled in entrepreneurship courses. Research shows that students gain a better understanding of financial management, business concepts and market strategies compared to students who do not have formal economic education, students who are exposed to economic materials are more likely to develop business innovations and take risks. Lack of hands-on experience and limited access to business resources are some of the obstacles that hinder the application of economic theory into entrepreneurial practice. This research helps educational institutions strengthen students’ entrepreneurial thinking by creating a curriculum that is more applicable and experience-based.